SPATIAL DISTRIBUTION OF GEOMORPHOLOGICAL UNITS IN THE GUNUNGSUNGGING AREA, SUKABUMI REGENCY, WEST JAVA - Priyayi, Mitra; Pratiwi, Santi Dwi (Journal of Geological Sciences and Applied Geology, 2026)
The geomorphological landscape of southern Java has developed through long-term interactions between tectonic activity, lithological diversity, and surface processes related to the convergence of the Eurasian and Indo-Australian plates. One of the regions that records this complex evolution is the Ciletuh–Jampang area, which displays a variety of landforms associated with uplifted terrains and differential erosion. This study focuses on the Gunungsungging area, Sukabumi Regency, West Java, with the objective of identifying geomorphological characteristics and defining geomorphological units based on landform attributes and lithological control. Geomorphological analysis was conducted using an integrated approach combining morphographic, morphometric, and morphogenetic methods. Digital elevation data derived from SRTM were processed using ArcGIS and Global Mapper, and the results were validated through systematic field observations. Morphographic analysis indicates that the study area is dominated by low hill landforms with elevations generally ranging between 50 and 175 m above sea level. The drainage system exhibits two primary patterns: parallel drainage, developed on moderate slopes and elongated ridges, and dendritic drainage, commonly associated with more homogeneous lithology and gentler slopes. Morphometric analysis reveals that flat to gently sloping terrain (0°–4°) predominates across the study area, with steeper slopes occurring locally. Morphogenetic interpretation suggests that exogenous processes, particularly weathering and dissolution, play a dominant role in shaping the landscape, while the influence of tectonic activity is relatively limited, as evidenced by minimal structural deformation. Karstification features, including caves and dissolution forms, are well developed within limestone unit. Based on the integration of geomorphological parameters, the study area is divided into three geomorphological units: gently sloping structural low hills, gently sloping denudational low hills, and gently sloping karst low hills. These results contribute to a better understanding of landscape development in the Ciletuh region and provide a geomorphological framework for further geological and environmental studies.